Recouvrir les ossements : L’archéologie du respect sur la rivière Kazan, Nunavut - T. Friesen; Andrew Stewart (Études Inuit Studies, 2019)
Complex relationships between people and animals define life in the northern past. For Inuit these relationships are manifested in many ways, particularly in practices that are often described as showing respect for animals, thus promoting stable relations between animal and human societies. Frustratingly, many of these activities, which are so prominent in the ethnographic record, have few archaeological correlates. Here, we examine one important practice with a relatively high level of archaeological visibility: the concealment of caribou bones under stones and in other inaccessible areas, which thereby protect them from dogs and other disturbances that could offend the caribou’s inua (spirit, soul). We examine this phenomenon at several important caribou crossings and elsewhere at inland Inuit archaeological sites on the Kazan River, southern Nunavut, where we have conducted extensive surveys. This research was performed in collaboration with Baker Lake community members who have direct knowledge of these localities, including aspects of bone disposal. Together, these studies reveal a cultural landscape in which the human–caribou relationship is omnipresent, not just in terms of features relating to hunting and storage, but also with regard to the spiritual connection between these two interdependent categories of being. Des relations complexes entre les hommes et les animaux définissent la vie dans le passé nordique. Pour les Inuit, ces relations se manifestent de nombreuses manières, notamment dans des pratiques souvent décrites comme des démonstrations du respect envers les animaux, favorisant la stabilité des relations entre les sociétés animales et humaines. Il est exaspérant de constater que beaucoup de ces activités, qui sont tellement proéminentes dans les archives ethnographiques, ont peu de corrélations archéologiques. Nous examinons ici une pratique importante présentant un niveau relativement élevé de visibilité archéologique : la dissimulation des os de caribou sous les pierres et dans d’autres ...